Efficiency of proposed teaching program based on (TRIZ) theory in developing critical thinking skills of science course, among female students at Grade six in Riyadh - Al-Anazi, Anwar Ayed; Al-Qumaizi, Hamad Abdullah (Journal of Curriculum and Teaching Methodology, 2023)
The aim of study is to reveal the Efficiency of proposed teaching program based on (TRIZ) theory in developing critical thinking skills of science course, among female students at Grade six in Riyadh. In order to achieve the aim of study, the semi-experimental approach were chosen for both experimental and control groups with a pre- and post test. The researcher prepared a test of critical thinking skills in the same unit of science course for grade six included an intended sample of (92) female students at primary school with a different intentional at (292) primary School for Girls in Education Department in Riyadh. The control group consisted of (47) students, while the experimental group included (45) students. After applying the pre- and post-study tool and processing the statistical data, the study concluded the following: The teaching program based on the theory of (TRIZ) in development. Critical thinking skills were effective. The study also presented a proposal for a teaching program based on the (TRIZ) theory of development Critical thinking skills from the science course for sixth grade students in Riyadh. (extraction, interpretation, analysis) for the sixth grade students in the science course, In light of the results, the study recommended several recommendations, the most important of which are: that the Student Activities Department in the education departments include in its training plan training programs on TRACE theory and critical thinking for female primary school students. Science teacher preparation programs in colleges of education should include topics on TRIZ theory and critical thinking and how to employ them in teaching science courses.